Spatial Typology of the Population Growth in European Union after 1990 - Ivan Šotkovský (European Regional Science Association (ERSA), 2011)
The article is deal with the demographic changes differences between European Union countries. We are research their population size changes during last 20 years. The spatial typology is given weigh of the three indicators: crude natural increase rate, crude net migration rate and crude total population increase rate. The analyses on this spatial level are working with the creation of cartogram method for processing of the demographical data. We can use ArcGIS 9.3 and his version ArcMap 9.3 as a complete system for authoring, serving, and using geographic informations for better processing the spatial data by the help of cartogram method. Our principal main is to group the all 27 EU countries on the basis population growing, population stagnant or population decreasing. Therefore we are using the basic measurement methods of the population numbers change (crude natural increase rate, crude net migration rate, crude total population increase rate). The world's current (overall as well as natural) growth rate is about 1.14%. The maximum of the total population growth on the EU territory was achieved during the period 2002 to 2008 (around value 4.4. ). The mean of the crude total population increase rate in the whole period 1990 to 2009 was 3 in the European Union. Sixteen countries from northern, western a southern Europe grew together more than the whole EU. Only eleven countries from central and south-eastern Europe had none population growth or visible loosed population size.
Keywords: 330